Infrared, X-Ray and Theromgravimtric Studies on Strontium Valerate, Caprylate and Laurate - Upadhyaya, S.K.; Rachna Nagar, Miss (Asian Journal of Chemistry, 2010)
The IR results showed that fatty acid exists in a dimeric structure as a result of hydrogen bonding between the carboxyl groups of two fatty acid molecules, whereas strontium soaps possess ionic character. The X-ray analysis showed that strontium soaps have single layer structure with molecular axes slightly inclined to the basal plane. The thermal decomposition of these soaps was found to be kinetically of zero order and the energy of activation for the decomposition process was in the range 38–63 KJ mol–1.